2017
DOI: 10.2147/ijn.s144579
|View full text |Cite
|
Sign up to set email alerts
|

rAAV-mediated overexpression of TGF-β via vector delivery in polymeric micelles stimulates the biological and reparative activities of human articular chondrocytes in vitro and in a human osteochondral defect model

Abstract: Recombinant adeno-associated virus (rAAV) vectors are clinically adapted vectors to durably treat human osteoarthritis (OA). Controlled delivery of rAAV vectors via polymeric micelles was reported to enhance the temporal and spatial presentation of the vectors into their targets. Here, we tested the feasibility of delivering rAAV vectors via poly (ethylene oxide) (PEO) and poly (propylene oxide) (PPO) (poloxamer and poloxamine) polymeric micelles as a means to overexpress the therapeutic factor transforming gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 46 publications
3
61
0
Order By: Relevance
“…[17][18][19] While work thus far emphasized on delivering shortlived nonviral [20][21][22][23][24][25][26][27][28][29][30] and potentially oncogenic lentiviral vectors, [31][32][33][34] there is still little information on transferring the more effective, clinically preferred recombinant adenoassociated virus (rAAV) vectors using biomaterials. 17,19,[35][36][37][38] Interestingly, most studies focused on the value of hydrogel systems for rAAV-based cartilage 6 regenerative medicine (fibrin, alginate, poloxamers, poloxamines, self-assembling peptides, polypseudorotaxanes), [39][40][41][42][43][44][45][46] while no evidence described the potential of mechanically stable solid scaffolds to guide rAAV application in sites of cartilage injury.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] While work thus far emphasized on delivering shortlived nonviral [20][21][22][23][24][25][26][27][28][29][30] and potentially oncogenic lentiviral vectors, [31][32][33][34] there is still little information on transferring the more effective, clinically preferred recombinant adenoassociated virus (rAAV) vectors using biomaterials. 17,19,[35][36][37][38] Interestingly, most studies focused on the value of hydrogel systems for rAAV-based cartilage 6 regenerative medicine (fibrin, alginate, poloxamers, poloxamines, self-assembling peptides, polypseudorotaxanes), [39][40][41][42][43][44][45][46] while no evidence described the potential of mechanically stable solid scaffolds to guide rAAV application in sites of cartilage injury.…”
Section: Introductionmentioning
confidence: 99%
“…Scaffold-assisted gene therapy is a powerful tool to durably and safely enhance the processes of cartilage repair [10][11][12] via single-step, controlled delivery of clinically adapted rAAV gene transfer vectors [25][26][27][28][29][30][31][32][33]. In the current work, we tested the ability of mechanically stable, biocompatible PCL scaffolds functionalized with a bioactive pNaSS molecule to transfer rAAV vectors coding for the cartilage-specific SOX9 transcription factor to human bone marrow aspirates as a means to generate more efficient, non-invasive systems to treat focal cartilage lesions compared with a less stable scaffold-free vector application lacking scaffolding benefits for the cell targets [42] or with complex, indirect transplantation of rAAV-modified aspirates via such materials [43].…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, a number of studies reported the potential of applying rAAV for experimental cartilage research via hydrogel systems (alginate, fibrin, poloxamers/poloxamines, self-assembling peptides, polypseudorotaxanes) [25][26][27][28][29][30][31][32][33] while there is still little information on the potential benefits of solid, mechanically more stable biomaterials that may provide scaffolding and stability to the target cells [34] for rAAV-mediated gene transfer. In this regard, we recently provided evidence that biocompatible solid polyester poly(ε-caprolactone) (PCL) [35], an aliphatic polyester approved by the FDA [36,37], further grafted with poly(sodium styrene sulfonate) (pNaSS) to activate reparative cellular responses [38] is capable of supporting the delivery of reporter rAAV gene vectors to effectively modify human bone marrow aspirates [39].…”
Section: Introductionmentioning
confidence: 99%
“…hMSCs were seeded in 24-well plates (2 × 10 4 cells/well) with growth medium for 12 h at 37 °C under 5% CO 2 . PolyCD-based nanoassemblies were then directly added to the cultures and live fluorescence was monitored in the samples by fluorescent microscopy using a rhodamine filter set (568 nm; Olympus CKX41; Hamburg, Germany) [ 55 , 57 ].…”
Section: Methodsmentioning
confidence: 99%